A STUDY OF POLITENESS IN BILLY CONDONS MOVIE “BEAUTY AND THE BEAST” - A, M Farid Dwinugroho; Iskandar, Iskandar; Sunra, La (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This study tries to examine how politeness is used in Bill Condon's film Beauty and the Beast. The film was picked since it is a live-action remake of the well-known Disney animated feature and has drawn a lot of interest from viewers all around the world. This study's primary goals are to identify the characters' politeness communication techniques and to examine the history and effects of politeness use in films. In this work, a case study technique is combined with a qualitative analytic method. The dialogues and details of the characters in the movie "Beauty and the Beast" are made up of the data. An analytical framework is provided by the politeness theory, which was created by authorities such as Brown and Levinson (1987) and Leech (1983). Data analysis was done by classifying the various forms of politeness that were employed. Positive manners (behavior that fosters amicable interactions between individuals)